Онтологічні аспекти інноваційної модернізації агропромислового виробництва України - Гончаренко, Оксана Володимирівна; Honcharenko, Oksana; Галаган, Тетяна Іванівна; Galagan, Tatyana; Самілик, Тамара Миколаївна; Samilyk, Tamara (Дніпровський державний аграрно-економічний університет, ТОВ `ДКС Центр`, 2023)
У статті здійснено аналіз, узагальнення сучасних тенденцій розвитку та визначені рушійні сили інноваційної модернізації агропромислового виробництва. Теоретико-методологічним базисом дослідження є системний підхід до визначення онтологічних особливостей розвитку агропромислового виробництва та обгрунтування напрямів його інноваційної модернізації. Акцентовано, що сільське господарство займає вагоме макроекономічне місце в національній економіці, воно забезпечує майже 11% ВВП та понад 40 % доходу національного експорту, в даній сфері були зайняті більш як 17% працівників. Обґрунтовано формування експортної спеціалізації агропромислового виробництва внаслідок його сировинної й вузько асортиментної орієнтації, що сформувалась під впливом та за присутності великого, переважно, іноземного капіталу. Аргументовано, що для корекції наявної моделі агропромислового розвитку не достатньо скористатися умовними перевагами періоду довоєнного розвитку (ґрунтово-кліматичними умовами, дешевою робочою силою, географічним положенням). Для модернізаційної трансформації необхідні ефективні базисні і спеціалізовані інститути, інституції та сформовані ними умови (ефективна й дієва правова система; інноваційно-інвестиційна, логістична та інформаційно-комунікаційна інфраструктура; освічений і кваліфікований людський капітал). Аргументовано, що стан аграрної галузі, який наблизився до "точки біфуркації" відкриває певні перспективи до відновлення або трансформації агропромислового виробництва до якісно іншого структурного формату, що ,потребує реалізації інструментів керованої інноваційної модернізації. Теоретико-методологічні положення проведеного дослідження поглиблюють практичні засади інноваційної модернізації агропромислового виробництва та його інституціонального забезпечення. The article analyses and summarizes modern development trends and identifies the driving forces of innovative modernization of agro industrial production. The theoretical and methodological basis of the study is a systematic approach to the definition of the ontological features of the development of agroindustrial production and the substantiation of directions for its innovative modernization. It was emphasized that agriculture occupies an important macroeconomic position in the national economy, it provides almost 11% of GDP and more than 40% of national export income, more than 17% of workers were employed in this field. The formation of export specialization of agro industrial production as a result of its raw material and narrow assortment orientation, which was formed under the influence and presence of large, mostly foreign capital, is substantiated. The mentioned has fixed the formed negative trend of agro industrial development, which reflects the inefficient commodity structure of trade with the predominance of sales volumes of unprocessed products and the reduction of the share of processed products. It is argued that in order to correct the existing model of agro-industrial development, it is not enough to take advantage of the conditional advantages of the prewar period of development (soil and climate conditions, cheap labourforce, geographical location). Modernization transformation requires effective basic and specialized institutions, institutions and the conditions formed by them (effective and efficient legal system; innovation and investment, logistics and information-communication infrastructure; educated and qualified human capital).It is emphasized that the financing of capital investments in the agrarian sector is dominated by own funds (90% of the total amount of investment), loans from the banking sector cover up to 9% of investment requests of farmers, and the share of budget funds does not exceed 1N3%. In the pre ar period of agricultural development, the investment potential of agricultural producers was determined by their financial condition and ability to attract credit resources. It is argued that the state of the agricultural sector, which has approached the "bifurcation point", opens up certain prospects for the restoration or transformation of agroindust rial production to a qualitatively different structural format, which requires the implementation of tools of managed innovative modernization. The theoretical and methodological provisions of the conducted research deepen the practical principles of innovative modernization of agro-industrial production and its institutional support.
Ontological aspects of innovative modernization of agricultural production of Ukraine
Keywords: агропромислове виробництво; agricultural production; модернізація; modernization; спеціалізація; specialization; інновація; innovation; розвиток; development; інститут; institute